The mitochondrial genome of one 'twisted-wing parasite' Xenos cf. moutoni (Insecta, Strepsiptera, Xenidae) from Gaoligong Mountains, Southwest of China. Issue 2 (1st February 2021) - Zhang, Ru; Li, Jun; Mao, Chuyang; Dong, Zhiwei; He, Jinwu; Liu, Guichun; Zhao, Ruoping; Wang, Wen; Li, Xueyan
Abstract: The nearly complete mitochondrial genome (mitogenome) of Xenos cf. moutoni, one twisted-wing parasite on wasp Vespa velutina from Southwest of China, is described in this study. The total length of this mitogenome is 16, 717 bp, containing 13 protein-coding genes (PCGs), 22 transfer RNA genes (tRNAs), two ribosomal RNA genes (rRNAs) and an incomplete A + T-rich control region . All of the 13 PCGs are initiated with canonical ATN (N represents A, T, G, C) as start codons; 8 PCGs are terminated with a complete typical stop codon TAA, and the remaining five PCGs ( cox2, cox3, nad3, nad4 and nad5 ) have an incomplete stop codon with just a T. The phylogenetic analysis based on the nucleotide sequences of PCGs and rRNAs indicates that Xenos cf . moutoni has a close relationship with Xenos vesparum, confirming its placement in the family Xenidae.